Strategi pengendalian penyebaran penyakit kolera dengan vaksinasi, edukasi, dan karantina: analisis model dan simulasi - Agusyarif Rezka Nuha; La Ode Nashar; Andi Agung; Bertu Rianto Takaendengan; Widyastutifajri Nuha (Mandalika Mathematics and Educations Journal, 2025)
Cholera is an infectious disease transmitted through water contaminated with Vibrio cholerae bacteria. This disease remains a public health challenge, especially in areas with poor sanitation. This study developed an SVIQR-B mathematical model to analyze the dynamics of cholera spread, taking into account the effects of quarantine, vaccination, and environmental hygiene education. The analysis was conducted on disease-free and endemic equilibrium points using a local stability approach based on the basic reproduction number (R0). The results showed that when R0 < 1 , the disease would disappear from the population, while R0 > 1 indicated the potential for endemicity. Sensitivity analysis and numerical simulation results indicate that an increase in the transmission rate and a decrease in vaccine effectiveness cause an increase in the value, while an increase in vaccination coverage and the effectiveness of education contribute to a decrease in infection rates. These findings emphasize the importance of implementing integrated medical and educational interventions in efforts to control cholera in a sustainable manner.